CORAK PEMIKIRAN FIQH LOKAL SYAIKH MAS’UD (1923-1994) KAWUNGANTEN CILACAP JAWA TENGAH (STUDI KITAB MASAILU SYATTA) - Mujiburrohman (LPPM STAI Nida El-Adabi, 2022)
This study aims to analyze the pattern of Shaykh Mas'ud's thoughts about fiqh in the Masailu Syatta book and the implications of these fiqh thoughts for the development of the scientific tradition of Islamic boarding schools and the treasures of Indonesian fiqh. The theoretical framework used in this study is the theory of discourse analysis in which there are three dimensions or stages in the process of analyzing reality, namely text, discourse practice, and social practice (socio-cultural practice). This study uses qualitative research methods with social history and ushul fiqh approaches. The data source used is the primary data source, namely the book Masailu Syatta by Shaykh Mas'ud and secondary data sources in the form of observations, interviews and documentation. Data analysis through descriptive-analytical, content analysis and historical methods. The findings of this study indicate that Syaikh Mas'ud's fiqh thinking has a school style that places more emphasis on the Shafi'i school. The method used can be seen from two aspects: first, his attention and sincerity in collecting as much fiqh literature as possible, especially in the Shafi'i school and second, a careful analysis of previous opinions by applying the maqashid syari'ah concept. His thoughts not only had a positive effect as a manifestation of the Islamic scientific tradition for Islamic boarding schools but also influenced the development of Shafi'i fiqh in the archipelago.